Análise espacial e caracterização da tuberculose após relacionamento entre sistemas de informação em saúde - Peres, Dalila Augusto (2016)
Tuberculosis (TB) Set up as hum public health problem worldwide, common to Brazil and Ceará, Influenced by HIV infection, increased resistance of bacilli TO Medicines and poor socioeconomic conditions of patients. A Strategy paragraph optimize the notification of cases and Information Systems Relationship Health, How the Information System for Notifiable Diseases (SINAN) and the Mortality Information System (SIM). The study aimed to characterize OS Cases of tuberculosis, increase, socio-demographic aspects, clinical, operational and spatial distribution After the SINAN and SIM Relationship, no state of Ceará. This was sectional study of cases and deaths from TB in 15+ years between 2005-2014, this state-residents. The Data Processing involved removing duplication of files and Case Relationship / Deaths FOR TB coinfection with cases AIDS / TB, through the SPSS software. The spatial distribution of tuberculosis hair was held ArcGIS version 9.3 program. There was a 2,325 increase (6%) APOS Relationship Between SINAN cases TB deaths FOR TB (primary or associated cause) SIM and coinfection Cases of TB / HIV in SINAN AIDS and Improvement of information concerning the criteria for closure and registration of Infection HIV. An analysis of prevalence and tuberculosis mortality showed decreasing trend, and coinfection prevalence of TB / HIV showed Trend Crescent. The observed outcomes show cure rate expected Below and decreasing trend, abandonment Greater than expected and Trend Crescent and High lethality with trend stabilization of deaths. This study defined priority areas Geographic For tuberculosis mortality BY control in Ceará and demonstrated That the geographic information system technology can be used in the planning and monitoring of programmatic actions tuberculosis. stand out as RECOMMENDATIONS: the death Research IN TB Epidemiological Surveillance cores Expansion and Data Relationship For Coordination municipal paragraph evaluate underreporting and timely capture of Cases For Health units.